PENGARUH PENAMBAHAN PUTIH TELUR TERHADAP KUAT TEKAN BETON - Tarantein, Debora; Sahusilawane, Tonny; Apalem, Delvia Rimesye (Journal Agregate, 2024)
The use of concrete as a building material has long been known in Indonesia. Basically, concrete is defined as a mixture of other hydraulic cement, fine aggregate, coarse aggregate and water with or without additional ingredients (admixture) which form a solid mass. Historically, egg white itself has been used as a mixture in concrete. Egg white contains calcium carbonate (CaCO3), magnesium oxide (Mg), iron oxide (Fe2O3) and phosphorus pentoxide (P2O5), which are also contained in cement. Egg white will be an added ingredient in the concrete mixture in this test with a percentage of added material used of 0%, 2% and 2.3% of the cement weight. The concrete test object is made in the form of a cube with dimensions of 15×15×15 cm and is made according to the SNI 03-2834-2000 method. The parameters to be tested are the slump test and the compressive strength of the concrete with a standard compressive strength of 200 Kg/cm² at a concrete age of 7 days. The results obtained in this research were that the compressive strength of concrete with 0% egg white added was 223.7 kg/cm2, 2% was 181,8 kg/cm2, and 2.3% was 221,1 kg/cm2. The slump test percentage values ​​are 0% = 9 cm, 2% = 10.8 cm and 2.3% = 8 cm. So it can be concluded that the use of egg white as an added material has an effect on compressive strength, because the more egg white added material in the concrete, the stronger the compressive strength of the concrete and the resulting slump test. It can be seen from the use of 2% added material which produces a compressive strength of 181,8 kg/cm2 and 2.3% yields 221,1 kg/cm2.